2022
DOI: 10.1111/cea.14098
|View full text |Cite
|
Sign up to set email alerts
|

Nasal administration of a probiotic assemblage in allergic rhinitis: A randomised placebo‐controlled crossover trial

Abstract: Background Topical probiotics have been suggested as a treatment option for allergic rhinitis, as they may skew the immune response towards a beneficial type‐1 non‐allergic profile. So far observations in man have exclusively involved oral intake. The aim of this study was to examine whether a topical/nasal administration of a probiotic assemblage (PA) affects quality of life, symptoms and signs of allergic rhinitis in a nasal allergen challenge (NAC) model. Methods In a placebo‐controlled and crossover design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The scores of the groups treated with Lactiplantibacillus plantarum, Lacticaseibacillus paracasei and Lacticaseibacillus rhamnosus strains were lower than those of the placebo group, with the MD of-5.19, -7.39 and -1.64, respectively. According to a meta-analysis, neither L. paracasei Lp33 nor L. rhamnosus GG had significant efficacy [17][18][19][20]. This may be due to the deviation caused by the lack of in-depth study of each strain.…”
Section: Species Used For Probioticsmentioning
confidence: 97%
See 3 more Smart Citations
“…The scores of the groups treated with Lactiplantibacillus plantarum, Lacticaseibacillus paracasei and Lacticaseibacillus rhamnosus strains were lower than those of the placebo group, with the MD of-5.19, -7.39 and -1.64, respectively. According to a meta-analysis, neither L. paracasei Lp33 nor L. rhamnosus GG had significant efficacy [17][18][19][20]. This may be due to the deviation caused by the lack of in-depth study of each strain.…”
Section: Species Used For Probioticsmentioning
confidence: 97%
“…This may be due to the deviation caused by the lack of in-depth study of each strain. In addition, researchers have suggested that in most cases, the combination of multiple strains is not more effective than a single strain [18][19][20][21]. This can remind clinicians that when treating patients with allergic rhinitis, they need to carefully consider the probiotic strains for treatment, and not blindly use multiple strains, otherwise it may not only fail to achieve a certain effect, but also bring new risks to patients.…”
Section: Species Used For Probioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies investigated the effects of oral administration of probiotics on AR, whereas few studies investigated the topical/nasal administration of probiotics. The topical application of microbiota was focused on by a recent randomized, double-blind, placebo-controlled, and crossover-involved clinical trial [ 231 ]. By intranasal administration, they composed a probiotic combination (PA) consisting of Lactobacillus rhamnosus SP1, Lactobacillus paracasei 101/37, and Lactococcus lactis L1A.…”
Section: Approaches For Restoring Epithelial Barrier In Nasal Diseasesmentioning
confidence: 99%